SAT0184 Therapeutic drug monitoring on rheumatoid arthritis patients with reduced doses of intravenous tocilizumab. (15th June 2017) - Ruiz-Esquide, V; Bastida, C; Pascal, M; Yagüe, J; Soy, D; Sanmartí, R
Abstract : Background: Tocilizumab (TCZ) is an effective treatment for rheumatoid arthritis (RA). Literature suggests there is great variability in intravenous (iv) TCZ serum concentrations among individuals. Moreover, optimal drug dosage does not seem to be clear since Regulatory Agencies (FDA and EMA) approved the drug with a different initial posology. Empirical dose de-escalation strategies are being fostered in patients with disease remission. Objectives: The purpose of the study was to examine TCZ serum concentrations at the different prescribed doses in RA. Secondary objectives were to evaluate the relationship between drug serum concentrations and laboratory parameters of disease activity. Methods: Prospective, observational, single-center study conducted in a university tertiary hospital. Enrolled RA patients received iv TCZ at a dose range from 4 to 8 mg/kg every 28 days. Demographic characteristics and clinical laboratory data were obtained at study entry. Blood samples for drug concentration testing were collected from the third TCZ dose onwards, just before TZC infusion and, when possible, once a week until the next drug administration. Results: 35 patients (88.6% women, 80% Caucasian) were included. Mean age ±SD was 54.1±12.3 and the median [range] of disease duration was 11.1 [2.9–48.5] years. Median treatment duration with iv TCZ was 36.5 [3–68] months. 54% of patients received the standard dose of 8mg/kg whereas the rest received reduced doses (23% were on 6mg/kg and 23% on 4mg/kg) due to persistent remission/low disease activity. 20 patients (57.1%) were being treated with low steroid dose and 24 (68.6%) were on concomitant DMARD, mainly methotrexate. Regarding drug concentration testing, a total of 109 samples were obtained. 19 patients participated to multiple drug sampling between two drug administrations and in the 17 remaining patients, a pre-dose sample was drawn. Mean TCZ concentrations are displayed in table 1 and showed in figure 1 . No significant differences were observed in median pre-dose TCZ concentration values (54 samples) between patients on 8 and 6 mg/kg whereas significant lower drug levels were observed in those taking 4 mg/kg. According to inflammatory parameters, mean C-reactive protein (CRP) concentration was significantly lower in those patients with trough TCZ concentrations >1μg/mL compared to those <1μg/mL (0.066mg/dL vs 0.689mg/dL, respectively; p<0.001). This difference was not observed with calprotectin serum concentrations (2.260μg/mL vs 2.143μg/mL). Conclusions: Trough TCZ serum concentrations do not differ between patients on an 8 and 6 mg/kg regimen. Therefore, according to the pharmacokinetics observed in our study, a maintenance dose of iv TCZ 6mg/kg would be appropriate for most RA patients. Although CRP levels are significantly higher in patients with trough iv TCZ concentrations <1μg/mL, serum calprotectin did not show the same tendency. Disclosure of Interest: None declared